1998
DOI: 10.1021/la980366d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Aggregation on the Binding of Lysozyme to Pyrene-Labeled Polyanions

Abstract: The binding of lysozyme to pyrene (Py)-labeled homo- and copolymers of sodium 2-(acrylamido)-2-methylpropanesulfonate and acrylamide was investigated by a combination of scattering techniques (turbidimetry, quasielastic light scattering, and electrophoretic light scattering), potentiometry, and fluorescence techniques. Lysozyme, a basic protein with a high isoelectric point of 11.5, is known to exist in a dimer form at ∼5 < pH < ∼10 and in an aggregate form at pH > ∼10. Potentiometric titration indicates bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 29 publications
(79 reference statements)
0
43
0
Order By: Relevance
“…The penetration of the specific HLH domain, embracing the amino acid residues Asp 87 -Arg 114 , into the lipid bilayers and subsequent disruption of membrane integrity have been demonstrated to be responsible for the bactericidal activity of Lz [24]. Furthermore, Lz antimicrobial action has been shown to be enhanced by modifying the charge and hydrophobicity of the protein [10,28]. In addition, Lz partially unfolded by heat treatment proved to exert catalytically independent antimicrobial action against both G+ and G-bacteria [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The penetration of the specific HLH domain, embracing the amino acid residues Asp 87 -Arg 114 , into the lipid bilayers and subsequent disruption of membrane integrity have been demonstrated to be responsible for the bactericidal activity of Lz [24]. Furthermore, Lz antimicrobial action has been shown to be enhanced by modifying the charge and hydrophobicity of the protein [10,28]. In addition, Lz partially unfolded by heat treatment proved to exert catalytically independent antimicrobial action against both G+ and G-bacteria [24].…”
Section: Discussionmentioning
confidence: 99%
“…Discovered by Alexander Fleming in 1922, lysozyme was the first protein whose three-dimensional structure was characterized at atomic resolution [1]. Owing to its well-defined geometry and physicochemical properties Lz represents an attractive model in approaching a broad spectrum of fundamental problems including protein adsorption at interfaces [2], lipid-protein interactions [3][4][5], membrane fusion [6,7], protein folding, aggregation and amyloid fibrillogenesis [8][9][10]. A number of studies provide evidence for pronounced lipid-associating ability of lysozyme [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Acrylic acid/ acrylamide, AA/AAm, (70/30) copolymer was purchased from General Science Co. (Tokyo), and dialyzed and freezedried before use. Poly(acrylamido-2-methylpropane sulfonate), PAMPS, and AMPS/AAm copolymers were prepared by polymerization of 2-(acrylamido)-2-methylpropanesulfonic acid with or without acrylamide as reported previously (41). Cetyltrimethylammonium chloride, CTAC, (Fluka) and Cetyltrimethylammonium bromide, CTAB, (Aldrich) were recrystallized twice from methanol.…”
Section: Methodsmentioning
confidence: 99%
“…The ''primary'' soluble complex consists of a number of proteins bound to a single polymer chain according to the previous report. 28 With the decrease of pH from 6.5 to 3.7, some SOD dimmers with a particle size of 20-30 nm occur in the free SOD solution, but the size of HA scarcely varies in the free HA solution. Therefore, a larger fluctuation of particle sizes directly indicates a variance of particle constituents for SOD-HA mixtures.…”
Section: Quasielastic Light Scatteringmentioning
confidence: 98%
“…[23][24][25][26][27] Fluorometry was carried out to observe nonradiative energy transfer during the binding process. 28 Isothermal titration calorimetry was performed to measure some important thermodynamic parameters, such as a binding constant, stoichiometry, enthalpy, and entropy. 29 Microcalorimetry experiments performed on the protein-polyelectrolyte systems, such as hyaluronic acid (HA)/poly(L-lysine) and bovine serum albumin/poly(allylamine hydrochloride), showed that counter ions were released in the complexation process, and the binding between polyanions and polycations was mainly entropically driven.…”
Section: Introductionmentioning
confidence: 99%